Isolation, characterization and genomic analysis of a novel lytic bacteriophage infecting Agrobacterium tumefaciens - Miloud SABRI; Kaoutar EL HANDI; Orges CARA; Angelo DE STRADIS; Toufic ELBEAINO (Phytopathologia Mediterranea)
Agrobacterium tumefaciens causes crown gall, and economic losses in important crops, including apple, pear, peach, and almond. Difficulties controlling this disease with conventional pesticides require alternative antibacterial agents. A novel lytic bacteriophage, Agrobacterium phage PAT1 (PAT1), with high lysis potential against A. tumefaciens, was isolated from wastewater. Interaction between PAT1 and A. tumefaciens cells was investigated using transmission electron microscopy. PAT1 adsorbed, infected, and replicated on A. tumefaciens in ≤30 min. Turbidity assays showed that PAT1 [Multiplicity of Infection (MOI) = 1] inhibited A. tumefaciens growth by 82% for 48 hours. PAT1 was resistant to broad ranges of pH (4 to 10) and temperatures (4 to 60°C). Bioinformatics analyses of the PAT1 genomic sequence showed that the bacteriophage was closely related to Atuphduovirus (Autographiviridae) phages. The PAT1 genome size was 45,040 base pairs with a G+C content of 54.5%, consisting of 54 coding sequences (CDS), of which the functions of 23 CDS were predicted, including an endolysin gene which could be used as an antimicrobial against A. tumefaciens. No lysogenic mediated genes or genes encoding virulence factors, antibiotic resistance, or toxins were detected in PAT1 genome. The bacteriophage showed potential as a biocontrol agent against A. tumefaciens infections, expanding the limited catalogue of lytic A. tumefaciens phages, although efficacy for control of crown gall in planta remains to be evaluated.